Inactive youth in sub-Saharan Africa: Does inequality of opportunity matter? - Mohammad Azhar Hussain; Atif Awad (Economies, 2022)
The present study seeks to find out how gender, age, area of living, parent background in terms of educational level and occupation determine the probability of youth to be out of the labour market in six Sub-Saharan Africa countries. We utilize data from the school-to-work transition surveys from 2014 and 2015 from the ILO. For each country, we first calculate a revised version of the Human Opportunity Index developed by the World Bank. Second, we compute the contribution of each factor to that index. The results show that dissimilarity has a marked influence in Madagascar and to some extent Malawi and Uganda, while the major challenges with getting the youth onto the labour market are still in Liberia even after taking dissimilarity of unchangeable background into account.
Keywords: 330; dissimilarity; employment; inequality of opportunity; youth